Examining the Influence of Covid-19 Pandemic on Female Students’ Education in Secondary Schools in Kisoro Municipality, Uganda - Hadijah, Nalule (Kabale University, 2022)
A Research Report Submitted to the Directorate of Postgraduate Training in Partial Fulfillment of the Requirements for the Award of the Degree in Master of Arts in Educational Management of Kabale University